Fibulin-5 (FBLN5) as a context-dependent pan-cancer regulator: integrated multi-omics analysis reveals dual roles in tumor progression and therapeutic resistance - Tong, Jingtao; Liu, Kaitai; Shi, Yajie; Dan, Yanggang; Hu, Bingchuan; Zhang, Hui (Translational Cancer Research; Vol 15, No 4 (April 30, 2026): Translational Cancer Research, 2026)
Fibulin-5 (FBLN5) is a key member of the extracellular matrix (ECM), which plays an important role in the occurrence and development of tumors. This study aimed to determine the role of FBLN5 in the diagnosis, prognosis, and immune regulation of tumors using a pan-cancer analysis.